The Influence of Self-Control on Phubbing Behavior among Vocational High School Students in West Jakarta - Ahiruddin, Ahiruddin; Ega, Ega Rachel Emmanuel; Rosada, Rosada (Asosiasi Asesmen Pendidikan (AAP), 2025)
Technological developments and the increasing use of smartphones have influenced adolescents' social interaction patterns, including the emergence of phubbing behavior, which is the tendency to ignore others because of focusing on mobile phones. Low self-control is suspected to be a contributing factor to this behavior. This study aims to determine the relationship between self-control and phubbing behavior among students of SMK Tri Arga 2 West Jakarta. The study used a quantitative approach with a simple random sampling technique and involved 200 students as a sample. The instruments used were the Self-Control Scale and the Phubbing Behavior Scale with a 4-point Likert model. All items were declared valid and reliable through validity tests and Cronbach's Alpha > 0.70. Data analysis used the Pearson Correlation test via SPSS version 26. The results showed a significance value of 0.000 (<0.05) and a correlation value of -0.570, indicating a significant and negative relationship between self-control and phubbing behavior. The higher the student's self-control, the lower the phubbing behavior they exhibit. The results of this study are expected to contribute to the development of guidance and counseling services, particularly in strengthening self-control as a preventive effort to reduce phubbing behavior in the school environment.